Critical thinking, university, history, knowledge, South Andean - Alanoca Arocutipa, Vicente (2017)
This editorial presentation refers to the National University of the Altiplano (Puno), knowing that it is not easy to analyze new or innovative social, political and cultural processes, in this case of the university system, because we live periods of cultural homogenization where diversity has been denied of languages and cultures. In this context, the development of critical thinking has become relegated with a sense of pertinence. It is known that the history of the UNA, passes through three relevant moments, such as the creation under an anchorage of positivism, then the reopening that was a tenacious struggle of the Puno region, and now embarked on the licensing process and with a great progress in the accreditation of vocational schools. There are challenges that must be met, especially considering research and intellectual production. The  Journal of Research Altoandinas, constitutes one of the doors of entry in the process of the reconstruction of critical thinking, where it develops themes framed within a plurality and freedom of thought that requires normative frameworks for the improvement of basic conditions quality and in the context of multicultural and linguistic diversity.